THE UNHCR ROLES FOR INCREASING REFUGEES TENACITY ON THE PANDEMIC COVID-19 ERA - Atikah Rahmi; Ummi Salamah; Faradila Umaya Nasution (Proceeding International Seminar of Islamic Studies, 2021)
In the principle, Indonesia has not been ratifying the United Nations conventions and protocols regarding the refugee status. Meanwhile, Indonesia becomes the transit state for the international refugees. Considering the human rights and non refoulment principles, Indonesia government protects the refugees, particularly in this pandemic era that is occurring globally. The refugees become vulnerable to the Covid-19 and suffering obstacles to obtain the rights fulfillment in the Pandemic era. The more complex problems occur among the refugees since they live in the crowded community with limited facilities. Moreover, some of the refugees have to struggle by themselves in order to maintain and protect them from Covid-19 while they do not get any support. A higher risk is experienced by women and children who become the victim of gender and sexual violence. As international organization, UNHCR and IOM, along with the Indonesia government should create a synergy and give serious attention for the international refugees to solve the problem. Through the normative law studies with qualitative data and previous studies, this article explains how UNHCR, IOM and Government respond and solve the refugee's problematique so that the refugee's in this pandemic era so that the refugees get appropriate protection.Keywords: UNHCR Actions, Refugee, Pandemic Covid-19